The shock of the new. Issue 2 (30th December 2019) - Dimson, Elroy; Marsh, Paul; Staunton, Mike
Abstract : Should investors put money into ground‐breaking industries? Or will they find that their enthusiasm is more likely to entice them into a market bubble that will soon burst? By Elroy Dimson, Paul Marsh and Mike Staunton